Evaluating Residual Activity in 18F-FDG administration - Santos, A (2014)
The Positron Emission Tomography (PET) is an imaging technique, based on functional, biochemical and molecular information. It is also a useful tool in oncological examination. 18F-FluoroDeoxyGlucose (FDG) is a radiopharmaceutical widely used in nuclear medicine departments with PET facilities. FDG’s corrects administration is very important in order to achieve good images and correct Standard Uptake Values (SUV). The aim of this study was to evaluate the residual activity, according to the method used in our department. Materials & Methods: Residual activities of the syringes used to administer FDG to 125 patients were measured and recorded, during one month. The intravenous administration was always performed by the same four nuclear medicine technologists. These technologists are trained in this procedure, according with the developed technique, based on the procedure guidelines for PET imaging. This technique consists in administering FDG in a catheter with a triple channel system (standard system with three-way tap to enable saline flush); the syringe is always filled to its maximum capacity (5cc) and rinsed once, including needle rinsing. Registered time in every procedure was calibrated, in order not to include bias. Results: according to the analysis of the registered data, less than 1% of the activity calculated and measured for each patient remained on the syringe. Conclusions: regarding the search for the best administration procedure, we conclude that the technique used in our department results in a very low residual activity, meaning that it is an accurate technique that leads to reliable SUV values.